Advancing the Assessment of Muscle and Cerebral Hemodynamics using Near-InfraRed Spectroscopy - Fernandez, Cristianne. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Sergio Fantini.; Committee: Srivalleesha Mallidi, Robert Jacob, and Darren Roblyer.; Keywords: Biomedical engineering, and Optics.